Necessidades formativas dos coordenadores pedagógicos das unidades escolares de um agrupamento da Rede Pública Estadual Paulista - Carvalho, Alessandro Alves de (2022)
The pedagogical coordinator’s job consists of complex and distinct attributions related to collective work, being responsible for the pedagogical organization of the school, for teachers’ and their own training. Thus, starting by the researcher’s questions, who is a Pedagogical Coordinator of a Group of Public Schools in the State of São Paulo, this study aimed to analyse training needs of the pedagogical coordinators of a group of schools. Specific objectives were: to identify how the participant became pedagogical coordinators of their schools; to identify the challenges they face to accomplish their goals; to identify feelings and the situations that induced them during their work as pedagogical coordinators; and to define guidelines for a training proposal based on the participants’ perspectives. Theoretical basis used authors who discuss the role of pedagogical coordinators and school-centered training. This qualitative research used a questionnaire, delivered to six pedagogical coordinators who work in schools of one of the groups of the Education Department Region South-2, to collect data. Data were explored by hermeneutical analysis. Results showed the importance of continuous training for pedagogical coordinators in school contexts that considers affective dimensions. Participants’ statements presented the challenges they face in their routine. Research also allowed critical and reflexive look at practice, bringing new meanings to it, which resulted in a more investigative posture towards the work developed with pedagogical coordinators